The effect of governance quality on future economic growth: an analysis and comparison of emerging market and developed economies - Luana Enikő Misi Lopes; Natalie Packham; Ursula Walther (SN Business & Economics, 2023)
This paper examines the influence of the six World Governance Indicators (WGIs), as defined by the World Bank, on the real GDP growth of five emerging markets, the BRICS (Brazil, Russia, India, China, and South Africa) countries, and three advanced economies, the United States, Germany and Japan. The analysis is based on a panel data set containing the six WGIs along with further macroeconomic variables (government debt, external debt, current account balance, trade balance, budget balance, foreign exchange rate and short-term interest rate), with annual data from 1996 to 2018. We find that regulatory quality has a positive impact on economic growth, an effect that remains stable across all robustness tests. This indicates that a sound regulatory environment stimulates economic growth. We also find a negative impact of rule of law on economic growth, but this effect is not robust. The literature, however, documents a negative effect from income to rule of law, expressing that higher income does not necessarily lead to a demand for better institutions. A principal component analysis on the WGIs shows that governance is diverse across countries, while stable over time. The first two PCs capture more than 95% of the WGIs variance and are able to cluster emerging and developed markets.
Keywords: O11; O43; I30; C23; 330; Governance; Economic growth; Emerging markets; Regulatory quality